Combined inhibition of polyamine metabolism and eIF5A hypusination suppresses colorectal cancer growth through a converging effect on MYC translation. (10th April 2023) - Coni, Sonia; Bordone, Rosa; Ivy, Devon Michael; Yurtsever, Zuleyha Nihan; Di Magno, Laura; D'Amico, Rodrigo; Cesaro, Bianca; Fatica, Alessandro; Belardinilli, Francesca; Bufalieri, Francesca; Maroder, Marella; De Smaele, Enrico; et al.
Abstract: A key mechanism driving colorectal cancer (CRC) development is the upregulation of MYC and its targets, including ornithine decarboxylase (ODC), a master regulator of polyamine metabolism. Elevated polyamines promote tumorigenesis in part by activating DHPS-mediated hypusination of the translation factor eIF5A, thereby inducing MYC biosynthesis. Thus, MYC, ODC and eIF5A orchestrate a positive feedback loop that represents an attractive therapeutic target for CRC therapy. Here we show that combined inhibition of ODC and eIF5A induces a synergistic antitumor response in CRC cells, leading to MYC suppression. We found that genes of the polyamine biosynthesis and hypusination pathways are significantly upregulated in colorectal cancer patients and that inhibition of ODC or DHPS alone limits CRC cell proliferation through a cytostatic mechanism, while combined ODC and DHPS/eIF5A blockade induces a synergistic inhibition, accompanied to apoptotic cell death in vitro and in mouse models of CRC and FAP. Mechanistically, we found that this dual treatment causes complete inhibition of MYC biosynthesis in a bimodal fashion, by preventing translational elongation and initiation. Together, these data illustrate a novel strategy for CRC treatment, based on the combined suppression of ODC and eIF5A, which holds promise for the treatment of CRC. Highlights: Polyamine biosynthesis and eIF5A hypusination genes are upregulated in human CRC. Individual inhibition of ODC and DHPS decreases CRC cell proliferation without inducing apoptosis. Combined ODC/DHPS blockade synergistically inhibits CRC growth and induces apoptosis in vitro and in mice. Combined inhibition of ODC and DHPS causes apoptosis through a bimodal effect on MYC translation.